Peningkatan Hasil Belajar PAI dengan Model Problem- Based Learning (PBL) Untuk Meningkatkan Kerjasama Kelompok Siswa Kelas IV SDN16 Kampung Dalam - Dellianis, Dellianis (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN 16 Kampung Dalam in the learning of Q.S At-Tin through an interactive activity-based learning approach. The method used is Classroom Action Research (CAR) conducted in two cycles, consisting of planning, implementation, observation, and reflection. The results show an increase in the students’ average scores from 72.2% in Cycle I to 78.1% in Cycle II, with significant improvement in motivation, engagement, and collaboration aspects. This improvement aligns with the application of social learning theory and experiential learning approaches. The study concludes that active student engagement strategies can enhance students’ understanding of religious materials, particularly Q.S At-Tin.